Using Self‐ and Informant Reports in the Assessment of Personality Pathology in Clinical Settings—An Easy and Effective 1–2 Combination. (March 2015) - Miller, Joshua D.; Lynam, Donald R.
Abstract : Samuel's (2015 ) review convincingly demonstrates that the use of unstructured clinical interviews to arrive at diagnoses of personality disorders is problematic at best. For a variety of reasons, clinicians are unlikely to begin using semi‐structured interviews to arrive at more reliable and valid diagnoses. Given this, we suggest clinicians more routinely use self‐ and informant reports of personality pathology. We review evidence suggesting that extant concerns about the ability and willingness of the self and others to provide such reports are overstated. Further, we briefly review evidence supporting the validity and utility of such reports.